Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) dalam Pembelajaran PAI di SMP Negeri 12 Palembang - Dahirin, Dahirin; Shabran, Shabran (Indo-MathEdu Intellectuals Journal, 2023)
This study aims to understand the implementation of the Strengthening the Profile of Pancasila Students Project (P5) in Islamic Religious Education (PAI) learning at SMP Negeri 12 Palembang. The research employs a qualitative approach with a descriptive type. Data collection techniques include in-depth interviews, observations, and documentation. Data analysis techniques involve stages of data collection, transcription, coding, categorization, and drawing conclusions. Based on the results and discussions, the implementation process has been carried out well through stages of lesson planning, learning execution, and assessment and evaluation of learning. With good and comprehensive planning, the implementation of P5 in PAI learning not only enhances students' religious knowledge but also builds strong character in line with Pancasila values, preparing them to become citizens of integrity and responsibility. The implementation of P5 in PAI also helps students develop critical thinking skills, creativity, cooperation, and social concern. This is evidenced by increased student participation in class activities and their ability to relate religious values to everyday life and national contexts. Continuous assessment and evaluation of the P5 implementation are conducted